Ramelteon exposure and survival of critically Ill sepsis patients: a retrospective study from MIMIC-IV - Yun-Yang Han; Yu Tian; Bing-Cheng Zhao; Ke-Xuan Liu (BMC Anesthesiology)
Abstract Background The effect of ramelteon, a melatonin receptor agonist, on survival in septic patients remains unknown. The purpose of this retrospective cohort study was to explore the relationship between ramelteon exposure and survival outcomes in septic patients. Methods Data from septic patients admitted to the intensive care unit (ICU) were extracted from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, with patients categorized into ramelteon exposure and non-exposure groups based on the use of ramelteon. The primary outcome was 30-day mortality, and secondary outcomes included 90-day mortality, in-hospital mortality, length of ICU stay, and hospital stay. Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) were employed to address confounding variables. Kaplan–Meier (K-M) analysis and Cox proportional hazards regression models for stepwise regression were utilized to assess the impact of ramelteon exposure on survival. Results This study included 22,152 unexposed patients and 2,708 exposed patients, resulting in 2,607 matched pairs after PSM. Following PSM, ramelteon exposure was associated with significantly lower in-hospital mortality (11.6% vs.19.7%, p < 0.001), 30-day mortality (13.4% vs. 23.2%, p < 0.001), and 90-day mortality (22.1% vs. 30%, p < 0.001).K-M curves demonstrated a significant difference in 30-day and 90-day mortality between the two groups (P < 0.001), irrespective of PSM application. Both PSM (hazard ratio [HR] = 0.53, 95% confidence intervals [CIs] 0.47–0.61, p < 0.001) and IPTW models (HR = 0.59, 95% CI 0.50–0.70, p < 0.001) indicated a significant positive effect of ramelteon usage on 30-day mortality among septic patients compared to the non-exposure group. Conclusions This exploratory, retrospective study suggests an association between ramelteon exposure and reduced 30-day and 90-day mortality in septic patients compared with the non-exposure group. Considering the limitations of the retrospective design and the potential for unmeasured confounding, well-designed prospective studies and randomized controlled trials will be needed to confirm these findings.